Risk Factor Analysis on Contingency Costs of Phase I Wastewater Network Project in Bogor City - Doni Triatmojo; Henny Pratiwi Adi; Hermin Poedjiastoeti (Jurnal Indonesia Sosial Teknologi, 2025)
Contingency cost estimation is essential for construction project management to anticipate cost uncertainty due to various risks. This study analyzes risk-based contingency cost estimation in the Bogor City Phase I wastewater network system project. The background of this research is based on the need for accurate cost planning to avoid budget overruns and ensure project sustainability. The study aims to identify risk factors that affect contingency costs, group risks based on their degree of influence, and build a more accurate estimation model using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) approach. This study uses a mixed method, namely qualitative analysis through interviews and literature studies to identify risk factors and a quantitative approach by distributing questionnaires to project stakeholders. The data was analyzed using SPSS 25 and SmartPLS software to test the validity and reliability of the contingency cost estimation model. The study results show that the most significant risk in the pre-construction stage is licensing and design, while in the construction stage is procuring equipment/materials and force majeure factors. The highest contingency cost estimate is in the preconstruction stage, with a value of 11.02%. The study's conclusion confirms that risk mitigation in the early stages of the project is essential to reduce the impact of budget uncertainty. The implications of this study contribute to the management of construction projects by providing a more accurate risk-based contingency cost estimation model that can be used as a reference for stakeholders in planning and managing infrastructure projects.